Insomnia in elderly patients – various ways to manage - Trawka, Paulina; Bednarek, Hanna; Karło, Aneta; Hejnosz, Paweł; Walczak, Magdalena; Graczykowska, Karolina; Modlińska, Aleksandra; Kwietniewska, Milena; Szmelcer, Beniamin; Kulczyńska, Aleksandra; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2019)
Introduction: Impaired duration, rhythm and depth of sleep and wakefulness called insomnia is a common problem in the group of geriatric patients. About 50% of elderly people report insomnia.Material and Methods: The paper reviews literature using the EBSCO and Google Scholar databases. Articles have been analyzed using the keywords insomnia, elderly patients, prevalence and etiology, primary care, treatment, diet, physiotherapy. The article presents various methods to manage insomnia among the elderly.Results: The main treatment for insomnia includes pharmacological and non-pharmacological interventions or a combination of both. A very important aspect is proper dietary, physiotherapy treatment and physical activity.Conclusions: Effective management of sleep disorders improves the quality of life of patients struggling with this disorder and prevents the occurrence of depression and anxiety, which often coexist with insomnia.